DETERMINATION OF THE MASS-DEPENDENCE OF CADMIUM ISOTOPE FRACTIONATION DURING EVAPORATION - Wombacher F.; Rehkamper M.; Mezger K. (My University, 2004)
Mass fractionation laws relate the fractionation factor αA for one isotope ratio to the fractionation factor αB for a second isotope ratio of the same element, with a fractionation exponent β such that αA = αBβ. The exponent β defines the mass-dependence of the mass fractionation law and thus determines the slope of a mass fractionation line in linearized three isotope space. The generalized power law (GPL) defines β as a function of a variable exponent n. The laws that aim to describe equilibrium and kinetic isotope fractionations are special cases of the GPL with n = −1 and n → 0, respectively.